Reduction in seizure burden in a child with a A350V IQSEC2 mutation using heat therapy with a Jacuzzi. Issue 9 (30th August 2021) - Levy, Andrew P; Levy, Nina S; Heyman, Eli; Schertz, Mitchell; Genizi, Jacob
Abstract: A child with a A350V IQSEC2 missense mutation resulting in drug‐resistant epilepsy stops having seizures when he has a fever. We demonstrate that raising the body temperature of the child using a commercial Jacuzzi dramatically reduces his seizures and appears to improve his social behavioral interactions. Abstract : A child with a A350V IQSEC2 missense mutation resulting in drug‐resistant epilepsy stops having seizures when he has a fever. We demonstrate that raising the body temperature of the child using a commercial Jacuzzi dramatically reduces his seizures and appears to improve his social behavioral interactions.